Otimização multiobjetivo para alocação de geradores distribuídos, banco de capacitores e reatores limitadores de curto-circuito usando o MOGWO - Azeredo, Lucas Freire Santos (2021)
In view of the growing search for renewable energy sources, as well as the increased financing of this sector in Brazil, it is notable that the advantages of renewable energy are not restricted only to the reduction of environmental impacts, but also to the advantages that involve greater reliability, quality and efficiency of the electrical system. Parallel to this, it has to be said that the insertion of new generating sources in a network that was designed to operate in a unidirectional way can provide modifications in the power flow. In view of this, it is essential to study the impacts that these generating sources have on the electrical system. The work in question seeks to analyze the optimized allocation of distributed photovoltaic generation, capacitor bank and shortcircuit limiting reactors to minimize the short-circuit current, losses and the harmonic distortion rate of the 13, 34 and 123 node networks from IEEE (Institute of Electrical and Electronic Engineers) using MOGWO (Multi-objective Gray Wolf Optimizer). The analyzed networks were modeled in OpenDSS (Open Distribution System Simulation) and throughout the optimization process, it was found that the greatest reduction in the analyzed parameters - losses, harmonic distortion rate and short circuit current -,it is associated with the location and the number of devices that are allocated in the system.